Value Of Uric Acid In Patients With Chronic Kidney Disease In Pre-Dialysis Stage - Egamberdieva Dano Abdisamatovna, Daminov Botir Turgunpulatovich, Ruzmetova Iroda Arslanovna (International Journal of Advanced Science and Technology, 2020)
The study examined the relationship between uric acid levels and renal function, as well as its role as a prognostic marker of cardiovascular risk in chronic kidney disease. In a multivariate regression analysis, taking into account the adjustment of potential risk factors, the level of uric acid was a significant factor affecting the glomerular filtration rate. The results of the study showed that elevated serum uric acid levels are associated with a higher risk of renal dysfunction.